The Athenian Ephebeia in the Fourth Century BCE - Friend, John L., (Brill Studies in Greek and Roman Epigraphy, 2019)
Based on the comprehensive study of the epigraphic and literary evidence, this book challenges the almost universally-held assumptions of modern scholarship on the date of origin, the function, and the purpose of the Athenian ephebeia . It offers a detailed reconstruction of the institution, which in the fourth century BCE was a state-organized and -funded system of mandatory national service for ephebes, citizens in their nineteenth and twentieth years, consisting of garrison duty, military training, and civic education. It concludes that the contribution of the ephebeia was vital for the security of Attica and that the ephebes' non-military activities were moulded by social, economic, and religious influences which reflect the preoccupations of Lycurgus' administration in the 330s and 320s BCE.